EFFECTS OF BENGOH DAM CONSTRUCTION ON SEDIMENTATION AND EROSION IN THE SARAWAK KIRI RIVER 文莪大坝建设对左砂拉越河沉积和侵蚀的影响 - Mohd. Elfy, Mersal; Kuok King, Kuok; Po Chan, Chiu; Md. Rezaur, Rahman; Muhammad Khusairy, Bin Bakri; Chin, Mei Yun (Southwest Jiaotong University, 2022)
The Bengoh Dam was constructed to secure reliable raw water supply to Kuching and its surrounding areas until 2030. However, the changes in river morphology along the Sarawak Kiri River after the Bengoh Dam construction remain unknown. This research was conducted to study the impact of Bengoh Dam construction on erosion and sedimentation along the Sarawak Kiri River using InfoWorks River Simulation (RS). The novelty is to identify and predict the short- and long-term geomorphology changes along the Sarawak Kiri River over the course of a year. Two scenarios were created, namely, a) with Bengoh Dam b) without Bengoh dam. The model with the Bengoh Dam scenario will be further investigated for ten years of simulation. The five locations selected for comparison and discussion are Bengoh Dam, Bengoh, Danu, Git Village and Batu Kitang. After the dam was built, sediment transport would be hindered, resulting in riverbed alterations. These changes are influenced by the location and proximity to the Bengoh Dam. Simulation results revealed that a huge amount of sediment will be accumulated behind Bengoh Dam. Both scenarios showed that there would be erosion at Bengoh, immediately after the Bengoh Dam, due to a phenomenon known as “Hungry Water.” It is novel to discover that the sedimentation rate at Danu, Git and Batu Kitang, which are located downstream of the Bengoh Dam, has drastically decreased. The capacity of the Batu Kitang Submersible Weir (BKSW) reservoir is unaffected by the constructed Bengoh Dam; hence no dredging must ensure the security of Kuching’s water supply.